STRATEGI INVESTASI TERKINI : MENGHADAPI VOLATILITAS PASAR - Febbi Dian Amelia Sari; Mochammad Isa Anshori (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The capital market always pays more attention to investment stakeholders, so the research aims to find strategies that can be applied when volatility occurs in the capital market. This research uses the literature review method to investigate appropriate strategies for dealing with volatility through a systematic approach by collecting, reviewing and synthesizing several relevant previous studies. With a focus on managing funds in storing assets through investment in the capital market. Highlighting the latest strategies, the results obtained through the Literature Review show the effectiveness of using strategies based on investment objectives and managing funds in accordance with the risk profile of each investor. Thus, this article provides insight for investors to make the right decisions in facing challenges and opportunities to deal with volatility in the capital market.